First versus second drop of capillary blood for monitoring blood glucose: a meta-analysis and systematic review - Xiaowan Dong; Chen Zhang; Tiantian Wu; Baimei Zhu (Archives of Medical Science)
Introduction The accuracy of the first or second drop of capillary blood for blood glucose monitoring remains unclear. This meta-analysis aimed to compare and evaluate the accuracy of the first or second drop of capillary blood for blood glucose monitoring, to provide evidence for clinical blood glucose monitoring and nursing care.